Detecting Passive Radar Reflectors for Automotive Applications - Händel, Chris; Autioniemi, Matti; Konttaniemi, Heikki (Lapin ammattikorkeakoulu, 2019)
This report demonstrates and discusses results of passive roadside radar reflector practical tests carried out in Rovaniemi during winter period 2017-2018. The selection of the passive radar reflectors for actual automotive radar tests on the Aurora intelligent test road in Muonio has been made based on this report. This report has been developed in the Arctic Challenge research project. The Arctic Challenge research project is funded by the Finnish Transport Agency (FTA) and the Finnish Transport Safety Agency (TraFi). The project is part of the Aurora intelligent road project of the Finnish Transport Agency and the NordicWay2 project funded by the Connecting Europe Facility of the European Union. The testing weeks for the research project will take place on the 10-km-long test stretch of the Aurora Vt21 (E8) intelligent road section in the years 2017–2019. Furthermore, the project is part of the Traffic Lab cooperation. The contracting partners involved in the research project include Dynniq Finland Oy, Indagon Oy, Infotripla Oy, Lapland University of Applied Sciences Oy, Roadscanners Oy, Sensible 4 Oy and VTT Technical Research Centre of Finland Oy.